RESPONSE TO THE GROWTH AND RESULTS OF MICROGREENS BROCOLY PLANTED HYDROPONICALLY WITH VARIOUS PLANTING MEDIA AND ADDITION OF COCONUT WATER SOURCES OF NUTRITION AND HORMONE - Sulistiya Sulistiya (Agros Journal of Agriculture Science, 2021)
This study aims to: (1) determine the type of planting medium that is most suitable for the growth and yield of broccoli microgreens, (2) to determine the effect of coconut water on the growth and yield of broccoli microgreens. Experiments were arranged according to Factorial Completely Randomized Design (CRD) with further 5% BNJ test, with factor I: Media for planting consisted of 4 levels (M1: Media for rockwool planting, M2: Media for planting cocopeat, M3: Media for planting husk charcoal, M4: Media Sand planting Factor II: Coconut water application consists of 2 levels (S1: Spraying ordinary water, S2: Spraying coconut water with 100% concentration). Based on these two factors, 8 treatment combinations were obtained with 3 repetitions. The results showed: (1) The planting medium of cocopeat added with coconut water gave the best response to the growth and yield of microgreen broccoli cultured hydroponically compared to the planting medium of rockwool, husk charcoal, and sand, (2) The addition of coconut water as a nutrient and hormone able to increase the growth and yield of broccoli microgreen in all types of planting media tested. In this experiment, the addition of coconut water to the cocopeat growing medium in hydroponic culture was able to increase the growth of microgreen height to 12.20 cm with a wet weight of 340.20 grams. To achieve optimal microgreen growth and yields, further research is needed using a mixed planting medium of cocopeat and other growing media to overcome the weaknesses in cocopeat.